Impact of Low Fiber Diet on Gastrointestinal Disorders - Ari Fahrial Syam; Daldiyono Daldiyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Fiber is not digested or absorbed in the small intestine. The main site of action of fiber is in the colon. In the colon, fiber will increase stool output and frequency, increase stool water, dilute the colonic content, reduce the toxins, bile acid, increase colonic fermentation and also stimulate probiotic growth. Some meta-analysis of observational epidemiologic and case control studies have found a protective effect of dietary fiber against colon cancer that increase with intake. Therefore, the high fiber diet is healthy recommendation to prevent various gastrointestinal disorders.   Keywords: dietary fiber - colon cancer - constipation